2013
DOI: 10.1016/j.clcc.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of STAT3 Phosphorylation on the Clinical Effectiveness of Anti-EGFR–Based Therapy in Patients With Metastatic Colorectal Cancer

Abstract: These results underscore an impact of pSTAT3 on the clinical efficacy of anti-EGFR-containing chemotherapy regimens and support the prospective assessment of this biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…However, a previous comprehensive study by Morikawa and colleagues found no association between STAT3, a number of molecular characteristics and survival in a cohort of over 700 patients (33). Furthermore, it has also been suggested that STAT3 may have a role in not only induction of KRAS mutated tumours (53), but also in conferring chemoresistance in patients with KRAS wild-type tumours (54). Indeed, this would suggest that STAT3 is independent of such characteristics.…”
Section: P=0039)mentioning
confidence: 96%
“…However, a previous comprehensive study by Morikawa and colleagues found no association between STAT3, a number of molecular characteristics and survival in a cohort of over 700 patients (33). Furthermore, it has also been suggested that STAT3 may have a role in not only induction of KRAS mutated tumours (53), but also in conferring chemoresistance in patients with KRAS wild-type tumours (54). Indeed, this would suggest that STAT3 is independent of such characteristics.…”
Section: P=0039)mentioning
confidence: 96%
“…The inhibition of Bcl-2 and Bcl-xl expression and the increase in Bax protein level, thus, provide a mechanistic basis of apoptosis induction by TQ. The expression of anti-apoptotic proteins Bcl-2 and Bcl-xl is transcriptionally regulated by STAT3 (25), which is overexpressed in colon cancer (24,37). Persistent STAT3 activation increases the proliferation of colon cancer cells in culture and enhances the growth of colon cancer cell xenograft tumors in nude mice (38).…”
Section: Discussionmentioning
confidence: 99%
“…38,40,41 Importantly, STAT3 activation was recently identified as a potential predictive marker for resistance to anti-EGFR therapies in patients with mCRC and NSCLC. 42,43 Inhibiting STAT3 in combination with anti-EGFR therapeutics have also revealed promising data pre-clinically, emphasizing the potential benefit of targeting of STAT3 to optimize anti-EGFR therapy in the clinic. [44][45][46][47] Our present study utilizes a STAT3 transcriptional reporter to demonstrate that efficacy of anti-EGFR therapeutics correlates with their ability to inhibit STAT3 activation in culture and in animal xenograft studies.…”
Section: Introductionmentioning
confidence: 97%